Method for improving antifriction and wear resistance of copper-based bearing bush

By forming an intermediate layer on the copper-based bearing shell and spraying a solid lubricating coating, the problem of insufficient self-lubricating and wear resistance of copper-based bearing shells in harsh environments is solved, and friction stability and wear resistance are significantly improved.

CN119500525APending Publication Date: 2025-02-25HENAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411645481.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, it is difficult to maintain good self-lubricating and wear resistance in harsh working environments, and the adhesive performance between the coating and the substrate is insufficient, resulting in poor friction stability and wear resistance.

Method used

By milling the substrate surface of the copper-based bearing shell to a roughness of 0.8≤Ra≤1.5, an intermediate layer is formed, and a wear-resistant coating is sprayed on the surface of the intermediate layer. After curing, a solid lubricating coating with a thickness of 20-30 μm is formed, which improves the adhesion performance and friction stability of the coating and the substrate.

Benefits of technology

The friction stability and wear resistance of copper-based bearing shells are significantly improved. The friction coefficient under dry friction conditions is 0.080, the wear rate is 0.20×10-5mm3/(N·m), the friction coefficient under oil lubrication conditions is 0.018, and the wear rate is 1.43×10-8mm3/(N·m).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500525A_ABST
    Figure CN119500525A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving antifriction and wear resistance of a copper-based bearing bush, which comprises the following steps of: milling the surface of a copper-based bearing bush substrate, and heating the milled copper-based bearing bush to 100 DEG C; then the copper-based bearing bush is placed in a polyethylene maleic anhydride solution to be soaked, the copper-based bearing bush is taken out and aired, and an intermediate layer with the thickness being 20-50 nm is formed on the surface of the copper-based bearing bush; and finally, repeatedly spraying a wear-resistant coating on the surface of the middle layer, and then carrying out curing treatment, so that a solid lubricating coating with the thickness of 20-30 microns is formed outside the middle layer. A preparation method of the wear-resistant coating comprises the following steps: uniformly mixing Al2O3, PTFE (Polytetrafluoroethylene) and phenolic aldehyde according to a mass ratio of (0.9-1.2): (0.8-1): 1, and impregnating the surface of the mixture with a coupling agent to obtain a mixture; adding the mixture, the dispersing agent and the flatting agent into the epoxy resin solution, and uniformly stirring; and then adding a curing agent to obtain the wear-resistant coating. According to the method, the bonding performance of the coating and the matrix can be improved, and the friction stability and the wear resistance can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a method for improving the friction reduction and wear resistance of a copper-based bearing bush. Background Art

[0002] The bearing is a key component where the sliding bearing contacts the rotating shaft. During the operation of the sliding bearing, the bearing and the rotating shaft will experience dry friction or oil-lubricated friction. Due to factors such as insufficient lubrication, overload, high temperature, lubricating oil contamination or abnormal viscosity under start-stop conditions, the bearing may suffer from ablation, increased wear and bearing damage. Therefore, the bearing needs to have excellent self-lubricating and wear-resistant properties. Since copper alloys show certain limitations under dry friction conditions, bearings consisting only of steel back and copper alloy layers can hardly adapt to harsh working environments. In order to effectively reduce the wear on the bearing surface, improve its friction stability and extend its service life, it is particularly important to develop solid lubricating coatings to enhance the surface properties of the bearing.

[0003] In the prior art, Chinese patent publication number CN110066595A discloses a modified polyimide lubricating coating composition, a solid lubricating coating and its application, which has a certain friction reduction and wear resistance effect on the swash plate of the air-conditioning compressor and the bearing of the automobile engine, but does not involve how to improve the bonding performance between the coating and the substrate. Chinese patent publication number CN103849311B discloses a method for preparing a solid lubricating coating on a copper-based bearing, which has a low friction coefficient under both dry friction and oil lubrication conditions, but does not involve how to improve friction stability and wear resistance.

[0004] Based on this, it is necessary to design a copper-based bearing processing method that can not only improve the bonding performance between the coating and the substrate, but also improve the friction stability and wear resistance. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a method for improving the friction reduction and wear resistance of a copper-based bearing bush, which can not only improve the bonding performance between the coating and the substrate, but also improve the friction stability and wear resistance.

[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: A method for improving the friction reduction and wear resistance of a copper-based bearing, mainly comprising the following steps: Step 1: milling the surface of the copper-based bearing bush to a roughness of 0.8≤Ra≤1.5; Step 2: Place the milled copper-based bearing in an oven and heat to 100° C. Step 3, taking the copper-based bearing bush out of the oven, placing it in a polyethylene maleic anhydride solution for immersion, taking it out and drying it, so as to form an intermediate layer with a thickness of 20-50 nm on the surface of the copper-based bearing bush; Step 4: repeatedly spraying the wear-resistant coating on the surface of the intermediate layer, and then performing a curing treatment, that is, forming a solid lubricating coating with a thickness of 20-30 μm outside the intermediate layer; Wherein, the preparation method of the wear-resistant coating used in step 4 is: (1) Al2O3, PTFE and phenolic fillers are uniformly mixed in a mass ratio of (0.9-1.2):(0.8-1):1, and then the surface is impregnated with a coupling agent to obtain a mixture; (2) Add the mixture, dispersant and leveling agent into the epoxy resin solution and stir evenly; then add the curing agent to obtain the wear-resistant coating.

[0007] Furthermore, in step three, the solvent in the polyethylene maleic anhydride solution is acetone, and the mass fraction of the solute is 1 to 5 wt%.

[0008] Furthermore, in step (1), the particle size of Al2O3 is 300-500 nm, the particle size of PTFE is 3-10 μm, and the particle size of phenolic acid is 10-20 μm.

[0009] Furthermore, in step (1), in step (1), the coupling agent is a silane coupling agent, and the coupling agent is any one of γ-glycidyloxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0010] Furthermore, in step (2), the mass ratio of the epoxy resin solution to the mixture is (4-6):1.

[0011] Further, in step (2), in the epoxy resin solution: The selected epoxy resin is at least one of epoxy resin E51 and epoxy resin E44; The solvent is a mixture of dichloromethane and cyclohexanone in a volume ratio of (0.8-1.2):(0.9-1.5); The mass ratio of solvent to epoxy resin is (2-3):1.

[0012] Furthermore, in step (2), the dispersant is an ester dispersant, and the amount of the dispersant is 3wt% of the mass of the epoxy resin; the dispersant is any one of glyceryl monostearate and glyceryl tristearate.

[0013] Furthermore, in step (2), the leveling agent is an organic silicon leveling agent, and the amount of the leveling agent is 3 wt% of the mass of the epoxy resin; the leveling agent is any one of polydimethylsiloxane and modified siloxane.

[0014] Furthermore, in step (2), the curing agent is an acid anhydride curing agent, and the amount of the curing agent is 6 to 10 wt% of the epoxy resin mass; the curing agent is at least one of maleic anhydride and phthalic anhydride.

[0015] Furthermore, in step 4, the specific parameters during curing are: pressure of 0.2-0.4 MPa, temperature of 200-235° C., and time of 4-5 h.

[0016] Beneficial effects:

[0017] (1) The filler in the wear-resistant coating used in the present invention comprises Al2O3, PTFE and phenolic formaldehyde, wherein Al2O3 as a hard phase can improve the bearing capacity of the coating through crack deflection and crack pinning mechanisms; PTFE as a soft phase not only gives the coating excellent lubrication properties, but also can repair the surface defects of wear marks, greatly improving the friction stability; phenolic formaldehyde contains aldehyde groups, which can react with epoxy groups to increase the cross-linking of epoxy resin molecules, thereby improving the mechanical properties of the coating. Under the synergistic effect of the three, the friction coefficient under dry friction conditions is 0.080, and the wear rate is 0.20×10 -5 mm 3 / (N·m), the friction coefficient under oil lubrication condition is 0.018, and the wear rate is 1.43×10 -8 mm 3 / (N·m).

[0018] (2) After the copper-based bearing is preheated, it is immersed in a polyethylene maleic anhydride solution to obtain an intermediate layer. The anhydride groups in the polyethylene maleic anhydride can react with the oxides on the surface of the copper alloy to form carboxylates, and can also participate in the curing reaction of the solid lubricating coating. The intermediate layer tightly connects the substrate and the solid lubricating coating on both sides through chemical reactions, greatly improving the bonding performance between the coating and the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the surface morphology of the solid lubricating coating prepared in Example 1.

[0020] Figure 2 It is a curve of the change of the friction coefficient of the samples prepared in Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 over time under dry friction conditions.

[0021] Figure 3 This is the wear morphology of the solid lubricating coating prepared in Example 1.

[0022] Figure 4 This is a surface morphology image of the copper-based bearing surface in comparative example 1.

[0023] Figure 5 This is the wear morphology of the copper-based bearing surface in Example 1.

[0024] Figure 6 This is a surface morphology of the solid lubricating coating prepared in Comparative Example 3.

[0025] Figure 7 This is the wear morphology of the solid lubricating coating prepared in Comparative Example 3.

[0026] Figure 8 This is a surface morphology of the solid lubricating coating prepared in Comparative Example 4.

[0027] Fig. 9 This is the wear morphology of the solid lubricating coating prepared in Comparative Example 4. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] The present invention provides a method for improving the friction reduction and wear resistance of a copper-based bearing bush, and the specific steps are as follows: Step S1, milling the surface of the bearing bush substrate to a roughness of 0.8≤Ra≤1.5; Step S2, placing the milled copper-based bearing in an oven and heating it to 100°C; heating can not only increase the surface activity of the copper-based bearing, which is beneficial for the subsequent coating to adhere better to the surface of the copper-based bearing; but also promote the volatilization of acetone in the polyethylene maleic anhydride solution and accelerate the formation of the intermediate layer. Step S3, taking the copper-based bearing bush out of the oven, placing it in a polyethylene maleic anhydride solution for immersion, taking it out and drying it, so as to form an intermediate layer with a thickness of 20-50 nm on the surface of the copper-based bearing bush; Step S4: preparing wear-resistant coating S41, mixing Al2O3, PTFE and phenolic fillers in a mass ratio of (0.9-1.2):(0.8-1):1, and then impregnating the surface with a coupling agent to obtain a mixture; S42, adding the mixture, dispersant and leveling agent to the epoxy resin solution, stirring evenly; then adding a curing agent to obtain a wear-resistant coating; Step S5, spray the wear-resistant coating prepared in step S4 on the bearing substrate by spraying, wait for the surface to dry, repeat the spraying and drying steps, and after reaching the target thickness, perform curing treatment. The curing pressure is 0.2-0.4MPa, the temperature is 200-235°C, and the time is 4-5h. After forming, a solid lubricating coating with a thickness of 20-30μm is formed outside the intermediate layer.

[0030] Wherein, in step S3, the solvent in the polyethylene maleic anhydride solution is acetone, and the mass fraction of the solute is 1 to 5 wt%.

[0031] In step S41, the particle size of Al2O3 is 300-500nm, the particle size of PTFE is 3-10μm, and the particle size of phenolic is 10-20μm. Nanoscale Al2O3 can be used as a wear-resistant reinforcement phase due to its high hardness. Al2O3 of this size is not easy to cause stress concentration during the friction process, which reduces the risk of particles detaching from the coating and reduces the damage to the coating caused by abrasive wear. PTFE is a lubricating reinforcement phase, and its excellent ductility and low surface energy help reduce friction, but because of its poor adhesion to epoxy resin, too large a particle size will significantly reduce the load-bearing capacity and lead to an increase in the wear rate. Similarly, too large a phenolic particle size will also affect its complete reaction with the epoxy resin, thereby affecting the performance of the material.

[0032] In step S41, the coupling agent is a silane coupling agent, and the coupling agent is any one of γ-glycidyloxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0033] In step S42, the mass ratio of the epoxy resin solution to the mixture is (4-6):1.

[0034] In step S42, in the epoxy resin solution, the epoxy resin selected is at least one of epoxy resin E51 and epoxy resin E44; the solvent is a mixture of dichloromethane and cyclohexanone in a volume ratio of (0.8-1.2): (0.9-1.5); the mass ratio of the solvent to the epoxy resin is (2-3):1.

[0035] In step S42, the dispersant is an ester dispersant, and the amount of the dispersant is 3wt% of the mass of the epoxy resin; the dispersant is any one of monostearic acid glyceryl and tristearic acid glyceryl. The leveling agent is an organic silicone leveling agent, and the amount of the leveling agent is 3wt% of the mass of the epoxy resin; the leveling agent is any one of polydimethylsiloxane and modified siloxane. The curing agent is an acid anhydride curing agent, and the amount of the curing agent is 6-10wt% of the mass of the epoxy resin; the curing agent is at least one of maleic anhydride and phthalic anhydride. The dispersant can reduce the aggregation of lubricating fillers in the epoxy resin solution and make it evenly dispersed in the solution. The leveling agent can reduce the surface tension of the coating solution, improve the fluidity of the coating, and enable the coating to form a smoother and flatter surface. The function of the curing agent is to accelerate the curing of the epoxy resin.

[0036] The raw materials in the embodiments and comparative examples were provided by Luoyang Shenyu Molybdenum Industry Co., Ltd.

[0037] Example 1

[0038] This embodiment provides a method for improving the friction reduction and wear resistance of a copper-based bearing bush, and the specific steps are as follows: Step S1, milling the surface of the bearing bush substrate to a roughness of 0.8≤Ra≤1.5; Step S2, placing the milled copper-based bearing bush in an oven and heating it to 100° C.; Step S3, taking 2g of polyethylene maleic anhydride and 98g of acetone to prepare a polyethylene maleic anhydride solution with a solute content of 2wt%, taking the copper-based bearing bush out of the oven, placing it in the polyethylene maleic anhydride solution for immersion, taking it out and drying it, so that an intermediate layer with a thickness of 20nm is formed on the surface of the copper-based bearing bush; Step S4: preparing wear-resistant coating S41, mixing 2 g of Al2O3, 2 g of PTFE, and 2 g of phenolic fillers for 240 min, and impregnating a coupling agent (γ-glycidyloxypropyltrimethoxysilane) on the surface of the fillers to obtain a mixture; S42, adding 10 ml of dichloromethane and 10 ml of cyclohexanone to 10 g of epoxy resin E51, mixing by a magnetic stirrer, stirring for 20 min, to obtain an epoxy resin solution; S43, adding the mixture, dispersant (0.3g of glyceryl monostearate) and leveling agent (0.3g of polydimethylsiloxane) to the epoxy resin solution, stirring for 80min, so that the lubricating filler is fully dispersed in the epoxy resin solution; then adding curing agent (1g of maleic anhydride) and stirring for 10min to obtain a wear-resistant coating; Step S5, spray the wear-resistant coating prepared in step S4 on the bearing substrate by spraying, wait for the surface to dry, repeat the spraying and drying steps, and after reaching the target thickness, perform curing treatment. The curing pressure is 0.3MPa, and it is cured for 4 hours in an environment of 200°C to form a solid lubricating coating with a thickness of 30μm outside the intermediate layer.

[0039] Example 2

[0040] This embodiment provides a method for improving the friction reduction and wear resistance of a copper-based bearing bush, and the specific steps are as follows: Step S1, milling the surface of the bearing bush substrate to a roughness of 0.8≤Ra≤1.5; Step S2, placing the milled copper-based bearing bush in an oven and heating it to 100° C.; Step S3, taking 2g of polyethylene maleic anhydride and 98g of acetone to prepare a polyethylene maleic anhydride solution with a solute content of 2wt%, taking the copper-based bearing bush out of the oven, placing it in the polyethylene maleic anhydride solution for immersion, taking it out and drying it, so that an intermediate layer with a thickness of 30nm is formed on the surface of the copper-based bearing bush; Step S4: preparing wear-resistant coating S41, mixing 1.8 g of Al2O3, 1.6 g of PTFE, and 2 g of phenolic fillers for 240 min, and impregnating a coupling agent (γ-glycidyloxypropyltrimethoxysilane) on the surface of the fillers to obtain a mixture; S42, then add 10 ml of dichloromethane and 10 ml of cyclohexanone to 10 g of epoxy resin E51, mix with a magnetic stirrer, and stir for 20 min to obtain an epoxy resin solution; S43, adding the mixture, dispersant (0.3g of glyceryl monostearate) and leveling agent (0.3g of polydimethylsiloxane) to the epoxy resin solution, stirring for 80min, so that the lubricating filler is fully dispersed in the epoxy resin solution; then adding a curing agent (1g of phthalic anhydride) and stirring for 10min to obtain a wear-resistant coating; Step S5, spray the wear-resistant coating prepared in step S4 on the bearing substrate by spraying, wait for the surface to dry, repeat the spraying and drying steps, and after reaching the target thickness, perform curing treatment. The curing pressure is 0.3MPa, and it is cured for 3 hours in an environment of 230°C to form a solid lubricating coating with a thickness of 28μm outside the intermediate layer.

[0041] Example 3

[0042] This embodiment provides a method for improving the friction reduction and wear resistance of a copper-based bearing bush, and the specific steps are as follows: Step S1, milling the surface of the bearing bush substrate to a roughness of 0.8≤Ra≤1.5; Step S2, placing the milled copper-based bearing bush in an oven and heating it to 100° C.; Step S3, taking 2g of polyethylene maleic anhydride and 98g of acetone to prepare a polyethylene maleic anhydride solution with a solute content of 2wt%, taking the copper-based bearing bush out of the oven, placing it in the polyethylene maleic anhydride solution for immersion, taking it out and drying it, so that an intermediate layer with a thickness of 50nm is formed on the surface of the copper-based bearing bush; Step S4: preparing wear-resistant coating S41, mixing 2.2 g of Al2O3, 1.6 g of PTFE, and 2 g of phenolic fillers for 240 min, and impregnating a coupling agent (3-aminopropyltriethoxysilane) on the surface of the fillers to obtain a mixture; S42, then add 10 ml of dichloromethane and 10 ml of cyclohexanone to 10 g of epoxy resin E51, mix with a magnetic stirrer, and stir for 20 min to obtain an epoxy resin solution; S43, adding the mixture, dispersant (0.3g of tristearate glyceryl), and leveling agent (0.3g of polydimethylsiloxane) to the epoxy resin solution, stirring for 80min, so that the lubricating filler is fully dispersed in the epoxy resin solution; then adding curing agent (1g of maleic anhydride), stirring for 10min, i.e., obtaining a wear-resistant coating; Step S5, spray the wear-resistant coating prepared in step S4 on the bearing substrate by spraying, wait for the surface to dry, repeat the spraying and drying steps, and after reaching the target thickness, perform curing treatment. The curing pressure is 0.3MPa, and it is cured for 5 hours in an environment of 200°C to form a solid lubricating coating with a thickness of 30μm outside the intermediate layer.

[0043] Comparative Example 1

[0044] The only difference between Comparative Example 1 and Example 1 is that it does not include steps S1-S5, i.e. the original copper-based bearing.

[0045] Comparative Example 2

[0046] The only difference between Comparative Example 2 and Example 1 is that step S3 is not included.

[0047] Comparative Example 3

[0048] The difference between Comparative Example 3 and Example 1 is that no PTFE filler is added in step S41.

[0049] Comparative Example 4

[0050] The difference between Comparative Example 4 and Example 1 is that no Al2O3 filler is added in step S41.

[0051] The bearing shells obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests.

[0052] (1) Friction performance analysis

[0053] The bearings of Examples 1 to 3 and Comparative Examples 1, 3 and 4 were subjected to wear characteristics analysis under dry friction and oil lubrication conditions using an RTEC friction and wear tester. The test load was 15N, the rotation speed was 300rpm, the radius was 6mm, the time was 8min, the grinding ball material was 304 stainless steel ball, the ball diameter was 6.35mm, and the experimental temperature was room temperature. The results are shown in Figure 2 And as shown in Table 1.

[0054] Table 1 Friction performance test results

[0055] from Figure 2It can be seen that the solid lubricating coating obtained in Example 1 of the present invention has long-term stability under dry friction conditions, and the fluctuation of the friction coefficient is minimal when stable. This is because PTFE as a soft phase not only gives the coating excellent lubrication properties, but also can repair wear surface defects, greatly improving the stability of friction. As can be seen from Table 1 above, the friction coefficient and wear rate of the solid lubricating coatings obtained in Examples 1 to 3 of the present invention under dry friction and oil lubrication conditions are significantly lower than those of Comparative Example 1, Comparative Example 3, and Comparative Example 4, indicating that the solid lubricating coating of the present invention has excellent wear resistance and self-lubrication, and the formed lubricating coating can greatly improve the tribological properties of copper-based bearings.

[0056] (2) Bonding strength

[0057] The coating bonding strength was measured with reference to GB / T8554-1997 Scratch test method for adhesion of vapor deposited film to substrate. The bonding strength between the solid lubricating coating obtained in Examples 1 to 3 and Comparative Example 2 and the copper-based bearing was tested. The results are shown in Table 2.

[0058] Table 2 Binding strength test results Bonding strength / N Example 1 32.3 Example 2 30.3 Example 3 30.6 Comparative Example 2 20.2

[0059] As can be seen from Table 2 above, the solid lubricating coatings formed by the solid lubricating coatings of Examples 1 to 3 of the present invention have good bonding performance with the substrate. This shows that the polyethylene maleic anhydride not only has good bonding performance, but the anhydride groups therein can generate carboxylates with the oxides on the surface of the copper alloy. At the same time, the anhydride groups can also participate in the curing reaction of the epoxy coating, greatly improving the bonding performance of the coating.

[0060] (3) Surface morphology analysis

[0061] Figure 1 The surface morphology of the coating prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the filler is evenly distributed in the coating, without pores, cracks or other microscopic defects. Figure 4 This is the surface morphology of the copper-based bearing bush in comparative example 1. Figure 4 It can be seen that the original copper-based bearing surface is smooth, and holes appear in some areas. Figure 6 is the surface morphology of the solid lubricating coating prepared in Comparative Example 3. Figure 6 It can be seen that the coating surface is relatively smooth, the filler is evenly distributed, and there are no pores, cracks or other microscopic defects. Figure 8 is a surface morphology of the solid lubricating coating prepared in Comparative Example 4. Figure 8 It can be seen that the coating surface is relatively rough, the filler is evenly distributed, and there are no pores, cracks or other microscopic defects.

[0062] (4) Wear morphology analysis

[0063] Example 1 The morphology after wear is as follows Figure 3 As shown, it can be seen that the friction surface is relatively smooth. This can be attributed to the fact that Al2O3 enhances the load-bearing capacity of the coating, PTFE improves the lubrication performance of the coating, and phenolic greatly improves the mechanical properties of the coating. Figure 5 As shown in the figure, it can be seen that the friction surface is relatively rough, with furrows, cracks and large accumulations of wear debris. Figure 7 As shown in the figure, it can be seen that there are furrows, spalling pits and coating spalling due to stress concentration on the friction surface. Fig. 9 As shown, it can be seen that the friction surface is relatively rough, and a large amount of compacted wear debris appears.

[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the friction reduction and wear resistance of a copper-based bearing, characterized in that: The main steps are as follows: Step 1: milling the surface of the copper-based bearing bush to a roughness of 0.8≤Ra≤1.5; Step 2: Place the milled copper-based bearing in an oven and heat to 100° C. Step 3, taking the copper-based bearing bush out of the oven, placing it in a polyethylene maleic anhydride solution for immersion, taking it out and drying it, so as to form an intermediate layer with a thickness of 20-50 nm on the surface of the copper-based bearing bush; Step 4: repeatedly spraying the wear-resistant coating on the surface of the intermediate layer, and then performing a curing treatment, that is, forming a solid lubricating coating with a thickness of 20-30 μm outside the intermediate layer; Wherein, the preparation method of the wear-resistant coating used in step 4 is: (1) Al2O3, PTFE and phenolic fillers are uniformly mixed in a mass ratio of (0.9~1.2):(0.8~1):1, and then the surface is impregnated with a coupling agent to obtain a mixture; (2) Add the mixture, dispersant and leveling agent to the epoxy resin solution and stir evenly; then add the curing agent to obtain the wear-resistant coating.

2. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step 3, the solvent in the polyethylene maleic anhydride solution is acetone, and the mass fraction of the solute is 1-5 wt%.

3. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (1), the particle size of Al2O3 is 300~500nm, the particle size of PTFE is 3~10µm, and the particle size of phenolic acid is 10~20µm.

4. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (1), the coupling agent is a silane coupling agent, and the coupling agent is any one of γ-glycidyloxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

5. The method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (2), the mass ratio of the epoxy resin solution to the mixture is (4-6):

1.

6. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (2), in the epoxy resin solution: The selected epoxy resin is at least one of epoxy resin E51 and epoxy resin E44; The solvent is a mixture of dichloromethane and cyclohexanone in a volume ratio of (0.8~1.2):(0.9~1.5); The mass ratio of solvent to epoxy resin is (2~3):

1.

7. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (2), the dispersant is an ester dispersant, and the amount of the dispersant is 3wt% of the mass of the epoxy resin; the dispersant is any one of monostearate glyceryl and tristearate glyceryl.

8. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (2), the leveling agent is an organic silicon leveling agent, and the amount of the leveling agent is 3 wt% of the mass of the epoxy resin; the leveling agent is any one of polydimethylsiloxane and modified siloxane.

9. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step (2), the curing agent is an acid anhydride curing agent, and the amount of the curing agent is 6-10 wt% of the epoxy resin mass; the curing agent is at least one of maleic anhydride and phthalic anhydride.

10. A method for improving the friction reduction and wear resistance of a copper-based bearing according to claim 1, characterized in that: In step 4, the specific parameters during curing are: pressure of 0.2-0.4 MPa, temperature of 200-235°C, and time of 4-5 hours.

Citation Information

Patent Citations

  • A method for preparing solid lubricating coating on copper-based bearing bush

    CN103849311B

  • Modified polyimide lubricating coating composition, solid lubricating coating and application of coating

    CN110066595A